2009
DOI: 10.17221/84/2009-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of enterotoxigenic isolates of B. cereus in foodstuffs

Abstract: Brychta J., Smola J., Pipek P., Ondráček J., Bednář V., Čížek A., Brychta T. (2009): The occurrence of enterotoxigenic isolates of B. cereus in foodstuffs. Czech J. Food Sci., 27: 284-292.Enterotoxigenic Bacillus cereus was detected in a variety of meat stuffs (36), ready-to-cook products (5), and swabs (7). The bacterial colonies isolated from PEMBA agar were identified as B. cereus. The 85 isolates were examined for the enterotoxin production using both TECRA-VIA and BCET-RPLA kits (ELISA -47, RPLA -38). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Te existence of B. cereus in dairy plants can be attributed to diferent sources such as the cow udders, collecting containers, transportation systems, and milk powder in the case of recombined milk [60]. Teir presence in the processing equipment demonstrates that the cleaning and disinfection procedures have not been performed carefully on the production equipment [61] or that the methods and products used are not efcient enough. In a previous study, the spores of the isolates herein investigated were shown to have diferent lengths of appendages, the surface of the exosporium and spore hydrophobicity which enable these spores to adhere to stainless steel surfaces [32].…”
Section: Discussionmentioning
confidence: 99%
“…Te existence of B. cereus in dairy plants can be attributed to diferent sources such as the cow udders, collecting containers, transportation systems, and milk powder in the case of recombined milk [60]. Teir presence in the processing equipment demonstrates that the cleaning and disinfection procedures have not been performed carefully on the production equipment [61] or that the methods and products used are not efcient enough. In a previous study, the spores of the isolates herein investigated were shown to have diferent lengths of appendages, the surface of the exosporium and spore hydrophobicity which enable these spores to adhere to stainless steel surfaces [32].…”
Section: Discussionmentioning
confidence: 99%
“…This would clearly indicate that bacillus having specific phenotypic line. According to the above described methods, an isolated Bacillus strains, are identified for each strain separately with Ribosomal 16SrRNA gene-specific PCR, which allowed for seven strains (indicated in Figure 1) to be identified compare with molecular marker determined as B. cereus (Brychta et al, 2009;Beecher and Wong, 1994). From the group of Bacillus spp.…”
Section: Bacterial Morphology Chemical and Biochemical Testsmentioning
confidence: 99%
“…Emetic B. cereus is presumably unable to grow and produce their toxin cereulide below 10°C, or in the absence of oxygen (EFSA, 2005). The (ELISA) Enzyme linked immunosorbent Adsorbed, is an immunoreactions which can use in toxins detections, and these types is useful in certain strains of bacteria to detect toxins (Brychta et al, 2009). The genotypic and phenotypic heterogeneities of the genus Bacillus, evident already for a long time (Ash et al, 1993).…”
Section: Introductionmentioning
confidence: 99%